Experimentation and The Vanishing Point of Photography In Contemporary Art - Deden Hendan Durahman; Yasraf Amir Piliang; Irma Damajanti; Armein Z. R. Langi (Pelopor Publikasi Akademika, 2025)
Photography has established itself as a dominant force in contemporary art, yet its boundaries are continuously challenged by experimental practices that merge traditional photographic principles with elements drawn from fine art traditions, such as painting. This presents a critical issue: how can photography evolve conceptually and aesthetically without losing its fundamental identity? This research aims to develop a framework for creating photographic artworks that explore the representational limits of the medium through bold experimentation while preserving its core principles. Employing G. Sullivan’s framework of interpretation, structure, and critical inquiry, the study examines how experimental practices transform photography into photographic imagery, pushing the medium to its conceptual and aesthetic vanishing points. The findings reveal that at these boundaries, photographic imagery transcends traditional representation and evolves into an ideological foundation, demonstrating the medium’s capacity for profound conceptual expression. Despite these transformations, the study concludes that experimentation does not compromise the essential nature of photography—its unique ability to evoke ostensibly truthful memories. By identifying and analyzing these dynamics, the research underscores the enduring relevance and adaptability of photography in contemporary art, highlighting its potential to navigate new creative frontiers while maintaining its intrinsic connection to reality.